Perpustakaan sebagai sumber informasi untuk siswa dan mahasiswa - Supiana, Elis (Maliki Interdisciplinary Journal, 2025)
In the modern era, libraries have experienced increasingly complex functions and roles in line with societal culture and the dynamics of the educational ecosystem. Libraries are not merely repositories for books; they are also sources of information, providing broad access to knowledge in both physical and digital forms. Libraries also serve as the heart of the educational ecosystem, supporting learning, research, and the development of information literacy. The public also has the opportunity to broaden their horizons, improve their competencies, and access a variety of relevant resources tailored to their academic and professional needs. As library services evolve, the digitalization of library services has also evolved through the provision of electronic resources such as ebooks, journals, scientific databases, and digital repositories, enabling users to access information quickly, accurately, and in-depth. This development not only enriches the library's function as an information center but also increases the efficiency and effectiveness of the services provided. Furthermore, various studies show that optimal utilization of library services is significantly correlated with increased academic success. Collection quality, accessibility, information, digital literacy skills, and librarian support are all contributing factors to improved academic achievement. Therefore, libraries play a strategic role in facilitating academic success and the development of a knowledgeable society in today's digital age by providing relevant and reliable information.